MODEL PEMBELAJARAN RENANG GAYA BEBAS UNTUK PEMULA - Muhammad Faisal Lutfi Amri; Juni Isnanto; Al Ilham (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The objective of research and development is to develop a model for crawl swimming for beginners. Additionally, extensive data on the following topics are gathered through research and development: the creation and application of beginner Basic models, in addition to assessing the child's efficiency, attractiveness, and effectiveness. This technique was created through innovative work (R and D) led by Borg and nerve. The research and development subjects are 88 elementary school students. The stages of research and development are as follows: The questionnaire and a crawl swimming test, both instruments used in research and development, are used to collect data rates from primary school-aged children: 1) specifications for the analysis; 2) evaluation by experts (the initial product evaluation); 3) restricted to a small group (testing); and the primary test, which is the fourth one. Determine the crawl level of primary school-aged children prior to administering treatments in the form of models developed to crawl swimming, as well as the crawl level of elementary school-age children following treatment or treatments that crawl swimming model to development, in order to determine the model's effectiveness. After receiving specific treatment in the form of crawl swimming models, primary school students achieved a crawl swimming proficiency of 1387, while those who took the initial tests achieved a crawl swimming proficiency of 901. As a result, crawl swimming is a good way for elementary school students to improve their crawl swimming abilities. The outcomes of the development can be used to draw the following conclusions: 1) Grade young models can be created and used in real-world training to further develop skills. 2) Information about the primary young models that have been created demonstrated their viability and improvement results creep swimming for beginners.